Pengaruh Gaya Kepemimpinan Transformasional Kepala Sekolah Terhadap Perencanaan dan Pelaksanaan Pembelajaran di Sekolah Dasar - Nur Asirah (Yayasan Sembilan Pemuda Indonesia, 2026)
This study aims to analyze the influence of the principal’s transformational leadership style on lesson planning and instructional implementation in elementary schools. Transformational leadership is believed to foster a collaborative, innovative, and professional school culture that can enhance teachers’ performance in designing and implementing learning processes. This research employed a quantitative approach using a pre-experimental design with a One Group Pretest–Posttest Design. The participants consisted of 10 teachers at SDN 011 Teluk Dalam. Data were collected using questionnaires and observation sheets that had been previously validated. Data analysis was conducted by comparing pretest and posttest results to determine changes after the implementation of transformational leadership practices. The findings indicate that the principal’s transformational leadership style has a positive and significant effect on improving the quality of lesson planning and instructional implementation. Principals who inspire teachers, provide individualized support, and encourage innovation are able to enhance teachers’ effectiveness in designing and conducting learning activities. The novelty of this study lies in examining the direct impact of transformational leadership on classroom instructional practices at the elementary school level. The results provide practical implications for strengthening principals’ leadership competencies in order to improve the quality of basic education.